The Natural Semantic Meta-language of War and Conflict Resolution in Kalenjin (The University of Nairobi Journal of Language and Linguistics, 2026)
This paper addresses the issue of war and conflict resolution in Kalenjin and is motivated by the quest to understand the cultural perspectives surrounding war and the resolution of conflicts as evidenced by the Kalenjin language. This is done against the backdrop of the Natural Semantic Metalanguage, which aims to provide a culture-free understanding of cultural norms through the use of a universal metalanguage. Data for this study were sourced from interviews, narratives and other secondary sources such as books. From the data and interviews, we unravel the cultural terms, phrases, practises and metaphors that relate to war and conflict resolution in some Kalenjin communities. From the study, it is observed that the Kalenjin notions of war are expressed as pɔ̀:rjɛ́:t ‘warfare’ and lùɣɛ́:t ‘raids’, where the former is undertaken for protection and reprisals against the enemy, while the latter is undertaken and sanctioned spiritually for community growth and expansion. In this, the cultural script of mùrɛ́n ‘warrior’ is very important, and all males have to be prepared for this role through circumcision. In war, various weapons were used, and elders participated in blessing or sanctioning raids. Conflict resolution, meanwhile, was overseen by kì:rùɔ̀ɣík ‘adjudicators’ and it only involved rival community members and not outsiders. This was undertaken under special trees known as kà:bù:rw ɔ́ ‘place of shade’; in this resolution, elderly women could also participate through the use of nɔ̀:ɣìrwɛ́:t ‘staff’, which symbolized their authority. Most wars among the Kalenjin were undertaken through lùɣɛ́:t ‘raids’ where the community raided other communities to acquire livestock and for territorial expansion.
Keywords: war; conflict resolution; natural semantic meta-language; metaphors; cultural scripts